Evaluating a tablet application and differential reinforcement to increase eye contact in children with autism. Issue 1 (19th October 2015) - Jeffries, Tricia; Crosland, Kimberly; Miltenberger, Raymond
Abstract : We tested the effectiveness of a tablet application and differential reinforcement to increase eye contact in 3 children with autism. The application required the child to look at a picture of a person's face and identify the number displayed in the person's eyes. Eye contact was assessed immediately after training, 1 hr after training, and in a playroom. The tablet application was not effective; however, differential reinforcement was effective for all participants.